Correlates of HIV testing among men from the Democratic Republic of Congo: an analysis of the 2014 Demographic Health Survey. Issue 11 (1st November 2020) - Ilunga Tshiswaka, Daudet; Whembolua, Guy-Lucien; Nduka, Uzoma; Muvuka, Baraka; Hill, Aaron; Inungu, Joseph N.; Conserve, Donaldson F.
ABSTRACT: Human immunodeficiency virus (HIV) testing is a cornerstone in preventing HIV infections and accessing treatment for HIV. However, HIV testing remains low among men in the Democratic Republic of Congo (DRC). The purpose of this study was to assess the correlates of HIV testing among men in the DRC. Data from the 2014 DRC Demographic Health Survey were analyzed to assess the relationships between HIV testing and the correlates of HIV testing among 7830 men aged 15–59 years. Although more than half (4763 or 63.7%) knew of an HIV testing site, only one-sixth (1187 or 16.6%) reported ever being tested for HIV. The multivariate logistic regression indicated that men aged between 25 and 34 years were more likely to have tested for HIV than those aged between 15 and 24 years (aOR = 1.70; 95% CI: [1.23–2.34]). In addition, men with college experience were 5.47 more likely to have tested for HIV than men with no formal education (aOR = 5.47; 95% CI: [2.53–11.84]). The results highlight the need for a national HIV testing awareness and uptake campaign for Congolese men to increase HIV testing among this group and prevent HIV infections.